Cost-effectiveness of QuantiFERON-TB Gold In-Tube versus tuberculin skin test for diagnosis and treatment of Latent Tuberculosis Infection in primary health care workers in Brazil - Loureiro, Rafaela Borge; Maciel, Ethel Leonor Noia; Caetano, Rosangela; Peres, Renata Lyrio; Fregona, Geisa; Golub, Jonathan E.; Braga, José Ueleres (PloS one, 2019)
The goal of this study was to perform a cost-effectiveness analysis from the public health system perspective, comparing five strategies for Latent Tuberculosis Infection (LTBI) diagnosis in primary health care workers in Brazil. Analytical model for decision making, characterized by cost-effectiveness analysis. Primary Care Level, considering primary health care workers in Brazil. An analytical model for decision making, characterized by a tree of probabilities of events, was developed considering a hypothetical cohort of 10,000 primary health care workers, using the software TreeAge Pro™ 2013 to simulate the clinical and economic impacts of new diagnostic technology (QuantiFERON®-TB Gold in-Tube) versus the traditional tuberculin skin test. This model simulated five diagnostic strategies for LTBI in primary health care workers (HCW) in Brazil: tuberculin skin testing using ≥5 mm cut-off, tuberculin skin testing ≥10 mm cut-off, QuantiFERON®-TB Gold in-Tube, tuberculin skin testing using ≥5 mm cut-off confirmed by QuantiFERON®-TB Gold In-Tube if TST positive, tuberculin skin testing using ≥10 mm cut-off confirmed by QuantiFERON®-TB Gold In-Tube if TST positive. The outcome measures are the number of individuals correctly classified by the test and the number of Tuberculosis cases avoided. The most cost-effective strategy was the tuberculin skin test considering ≥10mm cut-off. The isolated use of the QuantiFERON®-TB Gold In-Tube revealed the strategy of lower efficiency with incremental cost-effectiveness ratio (ICER) of US$ 146.05 for each HCW correctly classified by the test. The tuberculin skin test using ≥10 mm cut-off was the most cost-effective strategy in the diagnosis of Latent Tuberculosis Infection in primary health care works in Brazil.